Experience With Regional Anesthesia for Carotid Endarterectomy at the N.V. Sklifosovsky Research Institute for Emergency Medicine - S. A. Mustafayeva; S. V. Zhuravel; I. P. Mikhailov; E. A. Korotkova (Неотложная медицинская помощь)
Acute cerebrovascular accident is one of the major causes of death and disability of patients around the world. In 30-40% of cases, the cause of ischemic stroke is an extracranial lesion of the brachiocephalic vessels. Carotid endarterectomy is the main technique for preventing cerebrovascular accident in carotid artery stenosis. General anesthesia with endotracheal intubation has been the method of choice since the widespread introduction of this type of surgical intervention into clinical practice and in most centers remains so to this day. At the same time, many authors report, that the use of general anesthesia with endotracheal intubation has limitations in a number of patients, namely, in the presence of an embologenic plaque in the operated internal carotid artery, severe coronary artery disease, decompensated aortic and / or mitral stenosis, low ejection fraction, heart rhythm and conduction disorders, severe chronic diseases of the respiratory system, as well as patient refusal for general anesthesia.THE AIM of the study was to show the possibilities of using regional anesthesia for carotid endarterectomy in a high-risk patient.RESULTS The use of regional anesthesia allows surgeons to avoid instability or abrupt changes in hemodynamics in the intraoperative period. Indications for its use are also cases of critical contralateral stenosis of the internal carotid artery when it is necessary to carefully consider the advisability of installing an internal stent.CONCLUSION The use of regional anesthesia made it possible to successfully perform carotid endarterectomy without cardiovascular events, neurological deficit and postoperative complications in a patient with relative contraindications to general anesthesia.